Crime Traps in Inclusive Economic Development - Meita Indah Fadilla; Gabriella Natalie Krista Anindita; Dini Hariyanti; Nauviero Farizi Syarif (Universitas Negeri Semarang, 2025)
Increased crime is frequently assumed to be an unavoidable consequence of economic growth and development. The impact of criminal activity creates new challenges within the community. The purpose of this research is to investigate how criminal activities affect Indonesia's inclusive economic development. Panel data using the Least Squares Dummy Variable (LSDV) method covering 34 Indonesian provinces from 2018 to 2022 were used in this research. The findings indicate that the specific types of crime, namely crimes against decency, crimes against freedom of the person, and crimes against public order, notably influence inclusive economic development. The findings indicate that crimes against life, crimes including embezzlement, fraud, and corruption; crimes against property, both violent and non-violent; crimes related to narcotics; and crimes against physical bodies do not exert a significant influence on inclusive economic development. This study underscores the necessity of a comprehensive strategy that prioritizes crime-prevention tactics and involves a variety of stakeholders to address the underlying causes of criminal activity.